2012
DOI: 10.1016/j.mayocp.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Role of Vascular Endothelial Growth Factor Inhibitors in Ophthalmology

Abstract: Vascular endothelial growth factor (VEGF) plays an important role in both physiologic and pathologic angiogenesis and contributes to increased permeability across both the blood-retinal and blood-brain barriers. After 2 decades of extensive research into the VEGF families and receptors, specific molecules have been targeted for drug development, and several medications have received US Food and Drug Administration approval. Bevacizumab, a full-length antibody against VEGF approved for the intravenous treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 91 publications
(69 reference statements)
2
113
0
6
Order By: Relevance
“…Since 2005, it has been used in ophthalmology to treat various conditions, including neovascular age-related macular degeneration, diabetic macular edema, retinal vein occlusions, and neovascular glaucoma (26) . Variable outcomes have been reported on the use of bevacizumab in CSC (13,16) , and the mechanism of action of bevacizumab in CSC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2005, it has been used in ophthalmology to treat various conditions, including neovascular age-related macular degeneration, diabetic macular edema, retinal vein occlusions, and neovascular glaucoma (26) . Variable outcomes have been reported on the use of bevacizumab in CSC (13,16) , and the mechanism of action of bevacizumab in CSC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, current treatments for DR are mostly intended to block VEGF, by laser treatment and by anti-VEGF drugs (Stewart, 2012). However, VEGF is a survival factor for retinal neurons which are vulnerable to ischemic insult (Nishijima et al, 2007).…”
Section: Neuroprotective Effects Of Cilostazol In Diabetic Retinamentioning
confidence: 99%
“…Fundamental initiating process involved in retinal vascular development is angiogenesis which is regulated by growth factors, extracellular matrix components and complex of anti-and pro-inflammatory cytokines, among which IL-6, CRP, IL-17, IL-18, TNFα, TGF-β, BDNF, NT4, PDGF, IGF-I, EGF, FGF, PKC -protein kinase C-and HIF-1 α are recognized as key factors in the development of ROP. They have ability to modulate angiogenesis in ROP and are involved in dysregulation of this pathological phenomenon mainly through up-regulating VEGF messenger RNA synthesis, in response to tissue hypoxia or inflammation [2][3][4]. Additionally, it has been revealed that the so-called Fetal Inflammatory Response (FIRS) is the result of chorioamnionitis, antenatal intrauterine as well as Candida infections which are important agents in pathogenesis of prematurity complications such as sepsis, Periventricular Leukomalacia (PVL), Intraventricular Hemorrhage (IVH), Necrotizing Enterocolitis (NEC) or bronchopulmonary dysplasia [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%